2019
DOI: 10.11121/ijocta.01.2020.00752
|View full text |Cite
|
Sign up to set email alerts
|

Route planning methods for a modular warehouse system

Abstract: In this study, procedures are presented that can be used to determine the routes of the packages transported within a modular storage system. The problem is a variant of robot motion planning problem.  The structures of the procedures are developed in three steps for the simultaneous movement of multiple unit-sized packages in a modular warehouse.  The proposed heuristic methods consist of route planning, tagging, and main control components. In order to demonstrate the solution performance of the methods, var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
0
3
0
2
Order By: Relevance
“…With regard to the category of storage and handling equipment, the regression results indicated that this category has significant influence (β = .589, p < .05) on the defective product reduction skills toward positively enhancing overall production efficiency. The result suggests that the optimal using of storage and handling equipment has a positive impact not only on defective product reduction skills, but also makes the material easily accessible, maximizing the utilization of space, and eliminates factory hazards (Dayıoğlu, 2020). On the other hand, Abu Jadayil et al (2017), Ibrahim et al (2008) confirmed that having suitable storage equipment can help significantly on enhancing overall production efficiency and increasing profitability for the manufacturing organizations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to the category of storage and handling equipment, the regression results indicated that this category has significant influence (β = .589, p < .05) on the defective product reduction skills toward positively enhancing overall production efficiency. The result suggests that the optimal using of storage and handling equipment has a positive impact not only on defective product reduction skills, but also makes the material easily accessible, maximizing the utilization of space, and eliminates factory hazards (Dayıoğlu, 2020). On the other hand, Abu Jadayil et al (2017), Ibrahim et al (2008) confirmed that having suitable storage equipment can help significantly on enhancing overall production efficiency and increasing profitability for the manufacturing organizations.…”
Section: Resultsmentioning
confidence: 99%
“…These periods are known as brief suspensions during long-term shipping or long-term storage, and they are designed to allow the stock to accumulate (Disha Experts, 2020). The design of each type of storage equipment, in tandem with its use in warehouse design, denotes a trade-off between diminishing handling expenses, by making material easily accessible, and taking full advantage of the utilization of space (Dayıoğlu, 2020). By investigating enhanced efficiency possibilities in storage equipment, most of the firms have designed proprietary packaging in a way that allows products and materials of a certain type to conserve space while in inventory (Disha Experts, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Creating flexible, modular routing plans that can be easily adjusted as project scopes expand or contract, typical in large-scale solar projects. This measure is focused more on the planning stage [57].…”
Section: Ro 6 Modular Route Planningmentioning
confidence: 99%
“…Lojistik, malların tedarikçilerden müşterilere kadar olan yolculuğunda nakliye ve depolama ile ilgili tüm faaliyetleri içine alan bir fonksiyondur. Bu fonksiyon sayesinde malzeme ve ürünler ilk çıkış noktasından ihtiyaç duyulduğu nihai tüketim noktasına taşınırlar [8]. Üretim ve dağıtımdaki ürünlerin ağırlık ve hacim olarak büyümesi lojistik operasyonlarına ilişkin alanlarda optimizasyon çalışmalarını çok daha önemli hale getirmiştir [9].…”
Section: Giriş (Introduction)unclassified